2020
DOI: 10.7759/cureus.9879
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Lethal Abdominal Compartment Syndrome due to Rapidly Expanding Ovarian Small Cell Carcinoma Pulmonary Type

Abstract: A 53-year-old woman presented with a rapidly growing pelvic mass suspected to be endometrial cancer due to endometrial biopsy showing grade 1 endometrioid adenocarcinoma. Due to severe aortic valve stenosis, she underwent a transcatheter aortic valve replacement (TAVR) for surgical optimization for a planned total abdominal hysterectomy, bilateral salpingo-oophorectomy, and tumor debulking. She was discharged on dual antiplatelet therapy with plans for future surgery, but was readmitted with abdominal distensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Gynecologic conditions are considered an unusual etiology for the abdominal compartment syndrome with a limited number of reports in the literature [ 4 , 5 ]. For example, Sieloff et al reported a lethal case of abdominal compartment syndrome due to rapidly enlarging ovarian carcinoma whose management was delayed because of the patient’s comorbidities and the atypical presentation with the absence of abdominal pain [ 5 ]. It should be noted that patients with abdominal compartment syndrome are typically very ill and are unable to convey their clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Gynecologic conditions are considered an unusual etiology for the abdominal compartment syndrome with a limited number of reports in the literature [ 4 , 5 ]. For example, Sieloff et al reported a lethal case of abdominal compartment syndrome due to rapidly enlarging ovarian carcinoma whose management was delayed because of the patient’s comorbidities and the atypical presentation with the absence of abdominal pain [ 5 ]. It should be noted that patients with abdominal compartment syndrome are typically very ill and are unable to convey their clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%